Electrical Discharge and Breakdowns. A Study of Carbon Dioxide - Avaheden, Johannes (My University, 2014)
Sulfur hexafluoride (SF6) is widely used in modern high voltage gas insulated equipment. Despite of its excellent electrical and thermal performance, it is known as an extremely strong greenhouse gas and therefore a replacement is needed. One of the potential candidates is carbon dioxide (CO2), however many questions still remain regarding the dielectric properties of CO2. Experiments were carried out in uniform and weakly non-uniform background fields to find conditions for breakdowns, together with streamer and leader inception and propagation in CO2 in various levels of the electric fields and pressures from 1 to 5 bar. Also fundamental characteristic of streamers and leaders, such as discharge channel radius, propagation length at different field conditions, etc. were determined. The gathered data allow for predictions of time lags and streamer velocities. The results are discussed based on the knowledge of streamers in air and SF6.
Keywords: Energi; Elektrofysik; Elkraftteknik; Energy; Electrophysics; Electric power engineering